Precise gene modification mediated by TALEN and single-stranded oligodeoxynucleotides in human cells. - Xiaoling Wang; Yingjia Wang; He Huang; Buyuan Chen; Xinji Chen; Jianda Hu; Tammy Chang; Ren-Jang Lin; Jiing-Kuan Yee (PLoS ONE)
The development of human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) facilitates in vitro studies of human disease mechanisms, speeds up the process of drug screening, and raises the feasibility of using cell replacement therapy in clinics. However, the study of genotype-phenotype relationships in ESCs or iPSCs is hampered by the low efficiency of site-specific gene editing. Transcription activator-like effector nucleases (TALENs) spurred interest due to the ease of assembly, high efficiency and faithful gene targeting. In this study, we optimized the TALEN design to maximize its genomic cutting efficiency. We showed that using optimized TALENs in conjunction with single-strand oligodeoxynucleotide (ssODN) allowed efficient gene editing in human cells. Gene mutations and gene deletions for up to 7.8 kb can be accomplished at high efficiencies. We established human tumor cell lines and H9 ESC lines with homozygous deletion of the microRNA-21 (miR-21) gene and miR-9-2 gene. These cell lines provide a robust platform to dissect the roles these genes play during cell differentiation and tumorigenesis. We also observed that the endogenous homologous chromosome can serve as a donor template for gene editing. Overall, our studies demonstrate the versatility of using ssODN and TALEN to establish genetically modified cells for research and therapeutic application.